Estudo do impacto da fotobiomodulação na qualidade óssea de alvéolo dental de ratos Wistar pós exodontia associada ou não à biomaterial scaffold - Dalapria, Vanessa (2020)
The bone graft added to the tooth socket immediately after tooth extraction prevents bone atrophy and deformity at the site of the loss of the element. Photobiomodulation speeds up the bone healing process; stimulates blood flow; activates osteoblasts; decreases osteoclastic activity and improves the integration of graft material with bone tissue. The improvement in the quality of the bone graft provides stability and longevity of the implants in oral rehabilitation. The objective of this work was to evaluate the impact of photobiomodulation on the bone quality of dental alveolus of Wistar rats after tooth extraction associated or not with the scaffold biomaterial. Histological analyzes, optical coherence tomography, microtomography and analysis of acid and alkaline phosphatases were performed. 48 animals were used, divided into 5 groups (n=12): Basal (without interventions); Control (tooth extraction); LED (Exodontia and LED λ = 850 nm); Biomaterial (extraction and biomaterial) and Biomaterial + LED (extraction, biomaterial and LED λ = 850 nm). The animals were euthanized in 15 and 30 days. ALP at 15 days improved bone formation for the Control and Biomaterial + LED groups (p = 0. 0086 and p = 0. 0379, Bonferroni) and at 30 days in the LED group compared to the other groups (p = 0. 0007, Bonferroni ), for ACP all groups obtained less resorption compared to the Basal group. Bone density showed a significant improvement in the Biomaterial + LED and Biomaterial group in relation to the control and LED groups (p <0.05, t-test) at 30 days. The volume increased in the Biomaterial, Biomaterial + LED and Basal groups in relation to the Control group at 15 days (p <0.05, t-test). And at 30 days, the Basal group had a higher volume compared to the Control and LED groups (p <0.05, t-test). The OCT and histological analyzes did not show statistical differences (p> 0.05, t-test) between the groups or between the times, but the clinical analysis showed healing improvement and bone maturation in the groups with LED. The LED did not show a significant improvement in alveolar bone quality, however the clinical results suggested a potential action for both improving tissue organization and accelerating bone maturation, allowing for future discussion and new studies that elucidate its performance in the quality of alveolar bone associated or not to the scaffold biomaterial.